(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: To evaluate the safety of the measles vaccine MVVAC produced by POLYVAC through pharmacovigilance activity. A post-vaccination adverse event is an abnormality of health, including injection site or systemic manifestations occurring after vaccination, not necessarily attributable to the use of the vaccine, including common post-vaccination reactions and serious post-vaccination adverse events The most common adverse events following administration of measles vaccine produced by POLYVAC are usually local symptoms such as itching, pain, swelling or redness or both swelling and redness at the injection site; systemic symptoms such as fever below 39°C and other symptoms (malaise, fatigue, loss of appetite). Subjects and methods: Collection and analysis of post-vaccination adverse events recorded from batches of measles vaccine MVVAC produced by POLYVAC and used in immunization in 2019- 2021. From there, evaluate the safety of this vaccine. Results: The measles vaccine MVVAC produced by POLYVAC and used from 2019 to 2021 had the following adverse event rates: fever ≤39 °C with a rate of 0.004%; swelling, redness at the injection site has a rate of 0.014% and other symptoms have a rate of 0.0016%. Conclusion: The measles vaccine MVVAC produced by POLYVAC and used from 2019 to 2021 meets the requirements for post-injection safety.